Partnerships in collaborative care - Smith, S.; Isenring, L.; Rice, V.; Baker, M.; Thompson-Butel, A.; Mitchell, G.; Bissett, M.; Zakrzewski, L.; Lenson, S.; Gallego, G.; Wright, Tony; Hughes, M.; et al. (Elsevier Australia, 2017)
This chapter describes frequently encountered roles that are required to support the delivery of contemporary practice in the care of individuals with a chronic illness and/or disability.